2021
DOI: 10.3390/agriculture11111031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Antinutritional Compounds and Nutraceutical Significance of Native Bean Species (Phaseolus spp.) of Mexican Cultivars

Abstract: Common beans (Phaseolus vulgaris), comba beans (Phaseolus lunatus), and ayocote beans (Phaseolus coccineus) are the most consumed beans worldwide. This work aimed to analyze the nutraceutical potential, antinutritional content, antioxidant activity, and physicochemical characteristics of 38 native bean accessions from South Pacific Mexico. Regarding size, the accessions collected from P. lunatus were the longest (15.31 ± 1.31 mm) and widest (11.04 ± 0.85 mm), while those of P. coccineus were of a greater thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…The differences in phenolic compounds, antioxidant activity and mineral concentrations in grains among and within P. lunatus, P. coccineus and P. vulgaris differed slightly from the patterns found by Alcázar-Valle et al (2021). For example, they did not find differences between P. coccineus and P. lunatus and in this study, the differences were evident in the seed coat and whole grains.…”
Section: Variation In the Contents Of Phenolic Compounds And Antioxid...contrasting
confidence: 80%
See 3 more Smart Citations
“…The differences in phenolic compounds, antioxidant activity and mineral concentrations in grains among and within P. lunatus, P. coccineus and P. vulgaris differed slightly from the patterns found by Alcázar-Valle et al (2021). For example, they did not find differences between P. coccineus and P. lunatus and in this study, the differences were evident in the seed coat and whole grains.…”
Section: Variation In the Contents Of Phenolic Compounds And Antioxid...contrasting
confidence: 80%
“…In this study, the improved varieties of P. vulgaris used as controls had lower concentrations of polyphenols in the seed coat, cotyledons and whole grains than the populations of P. lunatus and P. coccineus; however, for the anthocyanin Phenolic Compounds, Antioxidant Activity and Mineral Contents in Grains of Phaseolus lunatus L. and P. coccineus L. Landraces contents in the seed coat and whole grains, the behavior was reversed. Alcázar-Valle et al (2021) observed the same pattern in their comparison of the same three species. In the samples of P. coccineus evaluated by Alvarado-López et al (2019), the variation in polyphenols and flavonoids ranged from 1.29 to 2.07 mg GAE g -1 and from 1.08 to 1.61 mg QE g -1 , respectively and in this study, the variation ranged from 17.0 to 34.1 GAE g -1 and 1.13 to 2.32 mg EC g -1 , indicating that the populations evaluated have the potential to be used in plant breeding (Table 2).…”
Section: Variation In the Contents Of Phenolic Compounds And Antioxid...supporting
confidence: 59%
See 2 more Smart Citations
“…However, #2TT contained the highest level of total flavonoids (1.68 mg RE/g). Generally, the tested extracts exhibited low levels of flavonoids (<1 mg RE/g); however, different levels of total phenols and flavonoids in Phaseolus vulgaris samples have been observed in the literature [ 30 , 31 , 32 , 33 ]. In a recent paper by Rossi et al, the effects of germinating time and gastrointestinal digestion on the chemical composition and biological activities of two common Phaseolus vulgaris cultivars were analysed, revealing a strong correlation between their phenolic contents and soil composition [ 34 ].…”
Section: Resultsmentioning
confidence: 99%